Mineral-geochemical characteristics Cu-U-Au-manifestations in the Kon Ra region of the Kon Tum province, Vietnam - Minh Phuong Do; P. A. Ignatov; Thi Hong Phan; Duy Hung Nguyen; Duan Tran (Известия высших учебных заведений: Геология и разведка)
Background. Complex Au-Cu-U mineralization is found in the metamorphic rocks of central Vietnam in the zones of their contact with Triassic granite intrusions. It is localized in tectonic breccias and cataclasites, which affected Triassic granitoids and Precambrian metaskarn rocks. The greatest differentiation is observed for tectonically disturbed granites of the Hai Van complex and the metasomatically reworked zones of contacts of this complex with metacarbonate and metaultramafic rocks of the Kham Duc complex.Aim. To determine the mineral and elemental composition of complex occurrences of Cu, U and Au in Proterozoic rocks of the Kon Tum province of central Vietnam.Materials and methods. The work was based on the authors’ data obtained during fieldwork and analytical laboratory studies in the 2016–2019 period. The diagnostics of ore mineral composition was carried out using 60 polished sections. The chemical composition of ores was determined for 214 samples by ICP MS and for 374 samples by atomic absorption spectrometry at the Vietnamese Centre for Geological and Experimental Analysis in the city of Hanoi. The geochemical relationships of ore components were established by the method of multivariate statistical correlations.Results. The mineral composition includes pyrrhotite, pyrite, chalcopyrite, molybdenite, magnetite, martite, hematite, cubanite, marcasite, gold, xenotime, sphalerite, uraninite, chalcocite, covellite, goethite, malachite and limonite. According to the petrographic and petrochemical composition, the geological position and the data on isotopic age, the metamorphic formations of the Kham Duc complex can be considered as Neoproterozoic-Cambrian formations having experienced metamorphism in the Ordovician.Conclusion. A scheme of the sequence of mineral formation was outlined. ICP MS results of primary ores showed that, in addition to Cu, the formations under study contain concentrations of Co, Mo, U, Au, Zn, Ni, V, Y, La, and As. A positive correlation was found between Cu, U and Au. A model of hydrothermal ore formation was proposed.